Social Justice Competencies and Career Development Practices - Arthur, Nancy; Collins, Sandra; Marshall, Catherine; McMahon, Mary (Canadian Journal of Counselling and Psychotherapy, 2012)
The recent focus on social justice issues in career development is primarily conceptual in nature and few resources account for the challenges or successes experienced by career development practitioners. The purpose of this article is to report the results of a research study of career practitioners in Canada regarding the competencies they use to address the barriers experienced by their clients from nondominant cultural groups, as well as the competencies that that they would like to strengthen. Recommendations follow for supporting career development practitioners to translate the concept of social justice into active practices directly with clients and with the systems that influence service delivery.